One Origin of Digital Humanities - Nyhan, Julianne,Passarotti, Marco (Springer, 2019)
List of Figures.-List of Tables – Foreword.-Preface and Acknowledgements .-About the editors .-Chapter 1 Introduction, or Why Busa Still Matters. Marco Passarotti and Julianne Nyhan.-Chapter 2 A First Example of Word Index Automatically Compiled and Printed by IBM Punched Card Machines. Roberto Busa S.J. – Chapter 3 The Use of Punched Cards in Linguistic Analysis. RobertoBusa S.J. .-Chapter 4 The Main Problems of the Automation of Written Language. Roberto Busa S.J. .-Chapter 5 The Work of the “Centro per l’Automazione dell’Analisi Letteraria” in Gallarate, Italy. Roberto Busa S.J. .-Chapter 6 Linguistic Analysis in the Global Evolution of Information. Roberto Busa S.J. – Chapter 7 Latin as a Suitable Computer Language for Science. Roberto Busa S.J. .-Chapter 8 Cybernetics and the Possibilities of a New Human Being. Roberto Busa S.J. .-Chapter 9 Experienced-Based Results with Preparations for the Use of Automatic Calculation in Biology. Roberto Busa S.J. .-Chapter 10 The Function and Use of an Electronic Computer. Roberto Busa S.J. – Chapter 11 Human Errors in the Preparation of Input for Computers. Roberto Busa S.J. – Chapter 12 Models of Knowing and Speaking. Roberto Busa S.J. – Chapter 13 Thirty Years of Informatics on Texts: at What Point are We? What Opportunities for Research? Roberto Busa S.J. – Chapter 14 The Complete Works of St Thomas Aquinas on CD-ROM with Hypertexts. Roberto Busa S.J. – Chapter 15 To Do and to Cause to Do: Man and Machine. Roberto Busa S.J. .-Chapter 16 Interior Algorithms of Understanding by Reading. Roberto Busa S.J. – Chapter 17 Considering Myself as if I were a Computer. Roberto Busa S.J. – Chapter 18 Doing Philosophy on the Computer and Doing Philosophy with the Computer. Roberto Busa S.J. – Chapter 19 Roberto Busa S.J. Bibliography: 1949–2009 – Chapter 20 “A Tall, Stooping Figure in Black Crossing the Courtyard”: Philip Barras’ Recollections of Roberto Busa S.J. Philip Barras and Julianne Nyhan .-Index This book gathers, and makes available in English, with new introductions, previously out of print or otherwise difficult to access articles by Fr Roberto Busa S.J. (1913 - 2011). Also included is a comprehensive bibliography of Busa, an oral history interview with Busa's translator, and a substantial new chapter that evaluates Busa's contributions and intellectual legacies. The result is a groundbreaking book that is of interest to digital humanists and computational linguists as well as historians of science, technology and the humanities. As the application of computing to cultural heritage becomes ever more ubiquitous, new possibilities for transmitting, shaping, understanding, questioning and even imagining the human record are opening up. Busa is considered by many to be among the pioneers in this field, and his research on projects like the Index Thomisticus is one of the earliest known examples of a humanities project that incorporated automation; it continues to be widely cited and used today. Busa published more than 350 academic articles and shorter pieces in numerous languages, but despite the unquestionable importance of his early work for understanding the history and development of fields like humanities computing and computational linguistics, a large part of his canon and thinking remained inaccessible or difficult to access until this book
10.1007/978-3-030-18313-4
Keywords: Digital Humanities; Humanities—Digital libraries; Computational linguistics; Application software; History; Computers